Islamic Perspectitve On Money Market and The Operation of Sharia Money Market - Andri Soemitra; Rifki Rifki Ismal; Yaumul Khair Afif; Anggi Pratiwi Sitorus; Julfan Saputra; Sabarudin Chaniago (ITB AAS INDONESIA Surakarta, 2021)
This study focuses on the money market under sharia principles, which are financial transactions (without interest) in the short term carried out by money market participants or money market players. Due to the purchase of securities is only short term, the transaction is carried out on the basis of trust. The money market that is allowed is the money market that does not use the interest system, this is to avoid usury nasi‟ah because the loss (danger) of interest is greater than the benefit. In addition, because Islam prohibits the buying and selling of money as a commodity or speculation. The design of this research is quantitative based on published journals related to the theme in this study Islamic Perspective on Money Markets and Sharia Money Market Operations. This research method is a literature study using secondary data in the form of 20 published journals during the 2011-2021 period which have been published as scientific journals both nationally and internationally to find out Islamic views on money markets and Sharia money market operations. The results showed based on a literature study of 20 published national and international journals based on the year the majority of journals were published in 2016, there were 5 journals (25%), the majority of descriptive research types were 15 journals (75%), the majority of journal areas were from Indonesia, 12 journals (60%), and based on journal subjects, most of them are Islamic Money Market and Interbank Islamic Money Market with 6 journals each (30%).